Choosing Wisely: Determining performance of unjustified imaging in a large healthcare system - Leventer‐Roberts, Maya; Lev Bar‐Or, Ruth; Gofer, Ilan; Rosenbaum, Ziv; Hoshen, Moshe; Feldman, Becca; Balicer, Ran (International journal of clinical practice (Esher), 2021)
Aims The Choosing Wisely Campaign identifies procedures and treatments that lack clinical justification for routine use according to expert opinion and evidence‐based medicine. This study describes the rates and features of two such examples over a 10‐year period. Methods This is a cross‐sectional rolling cohort study between 2008 and 2017 in Clalit Health Services, the largest healthcare delivery system in Israel, with seven main hospitals and over 4.5 million members nationwide. All adult members who visited a Clalit Emergency Department (ED), and all children members who visited a Clalit ED for abdominal pain or appendicitis were eligible to be included in this study. Our measures were routine chest radiograph (CXR) in the context of pre‐admission assessment for adults and abdominal computed tomography (CT) to rule out appendicitis for children. Results Of the 3 689 869 adult visits without a clinical indication for a CXR, 9.1% or 337 058 of them received a chest radiograph. Of the 35 973 children visits for presumed appendicitis, 7.2% of them had no imaging performed, 82.3% had an ultrasound (US), 6.9% had an US followed by a CT, and 3.6% or 1293 of them received a CT. There were several independent risk factors such as BMI, hospital, sex, year and diagnosis that are associated with having imaging that is not clinically indicated. Conclusions Overall, this study found that diagnostic imaging practices are applied inconsistently by hospital and by population. Intervention efforts should be focused on subpopulations at greatest risk to further reduce exposure to such imaging. Choosing Wisely recommendations identify diagnostic imaging practices which may be clinically unjustified. This study demonstrates how electronic medical records can be used to provide very specific information regarding when and for whom Choosing Wisely recommendations are not followed. By using the results of this type of study, clinician managers and policy makers can fine‐tune their interventions to improve compliance of Choosing Wisely recommendations.